Modulation of TCR Signaling by Tyrosine Phosphatases: From Autoimmunity to Immunotherapy - Castro-Sanchez, Patricia; Teagle, Alexandra R.; Prade, Sonja; Zamoyska, Rose (Frontiers in Cell and Developmental Biology, 2020)
Early TCR signaling is dependent on rapid phosphorylation and dephosphorylation of multiple signaling and adaptor proteins, leading to T cell activation. This process is tightly regulated by an intricate web of interactions between kinases and phosphatases. A number of tyrosine phosphatases have been shown to modulate T cell responses and thus alter T cell fate by negatively regulating early TCR signaling. Mutations in some of these enzymes are associated with enhanced predisposition to autoimmunity in humans, and mouse models deficient in orthologous genes often show T cell hyper-activation. Therefore, phosphatases are emerging as potential targets in situations where it is desirable to enhance T cell responses, such as immune responses to tumors. In this review, we summarize the current knowledge about tyrosine phosphatases that regulate early TCR signaling and discuss their involvement in autoimmunity and their potential as targets for tumor immunotherapy.immunotherapy.